Causal association of gastroesophageal reflux disease with obstructive sleep apnea and sleep-related phenotypes: a bidirectional two-sample Mendelian randomization study - Qin, Shan; Wang, Chi; Wang, Xiaoqiu; Wu, Wenzhong; Liu, Chengyong (Frontiers in Neurology, 2023)
Background The interactions and associations between obstructive sleep apnea (OSA), sleep-related phenotypes (SRPs), and gastroesophageal reflux disease (GERD) are complex, thus it is hard to explore the effect and direction of causalities. Study objectives A bidirectional Mendelian randomization (MR) study was performed to explore causal associations of GERD with OSA and SRPs (including insomnia, morningness, sleep duration, ease of getting up, daytime napping, daytime dozing, and snoring). Methods First, we gathered summary statistics from publicly available databases. Subsequently, we identified single-nucleotide polymorphisms without strong linkage (r2 ≤ 0.001) by referencing relevant genome-wide association studies that met genome-wide significance criteria. Our primary analysis relied on inverse variance weighted to estimate the causal relationship. To ensure the validity of our findings, we also conducted several sensitivity analyses. These included MR Pleiotropy RESidual Sum and Outlier to detect and correct for potential pleiotropic effects, MR-Egger to assess directional pleiotropy, and weighted median analysis to further evaluate heterogeneity and pleiotropy. For the initial MR analysis, when causality was indicated by the results, instrumental variables that were significantly linked to the aforementioned confounding factors were removed. We will re-analyze the data after excluding outcome-related single nucleotide polymorphisms to confirm that the results are still consistent with the previous results. Results GERD was found to increase the risk of OSA (OR = 1.53, 95% CI = 1.37–1.70, p = 5.3 × 10−15), insomnia (OR = 1.14, 95% CI = 1.10–1.19, p = 1.3 × 10−10), snoring (OR = 1.09, 95% CI = 1.04–1.13, p = 6.3 × 10−5) and less sleep duration (OR = 0.94, 95% CI = 0.91–0.97, p = 3.7 × 10−4). According to the reverse-direction analysis, there is an elevated risk of GERD associated with OSA (OR = 1.07, 95% CI = 1.02–1.12, p = 0.005), insomnia (OR = 1.95, 95% CI = 1.60–2.37, p = 1.92 × 10−11) and snoring (OR = 1.74, 95% CI = 1.37–2.21, p = 4.4 × 10−6). Conclusion Genetic susceptibility to GERD can elevate the likelihood of experiencing insomnia, snoring, and OSA, in addition to diminishing sleep duration. Conversely, a reverse MR analysis indicates that ameliorating any one of insomnia, snoring, or OSA can mitigate the risk of developing GERD.